Electrically driven heartbeat effect of gallium-based liquid metal on a ratchet - Wang, Shutong; Zhang, Yue; Wang, Jiuyang; Ren, Dongmei; Yu, Zhenwei (Frontiers in Bioengineering and Biotechnology, 2023)
The realization of the liquid metal heartbeat effect shows better controllability under nonperiodic stimuli compared with spontaneous oscillation or periodic stimuli. However, adjusting the liquid metal heartbeat performance, drop spreading area and frequency, solely by the magnitude of the voltage has great limitations. Here, we demonstrate that eGaIn drop can beat inside graphite ring electrodes under DC voltage in alkaline solutions on ratchet substrates. Those sawtooth structures provide asymmetric textures which influence the liquid metal deformation during the heart beating. We achieved heartbeat frequencies from 2.7-4.8 Hz, a 100% increase in the tunable frequency range compared to that on a flat surface. The oxidative spreading of the eGaIn drop on the ratchet substrate shows that the drop penetrates into the grooves of the sawtooth structure. Moreover, we investigated the physical mechanisms affecting the eGaIn heartbeat frequency, as well as the influence on the spreading area of the eGaIn drop at various sawtooth sizes and orientations. These findings not only enhance our understanding of droplet manipulation on sawtooth-structured surfaces but also facilitate the design of microfluidic pump systems.